Oxford studies in early modern philosophy. Volume VI - Garber, Daniel, 1949-; Rutherford, Donald, 1957- (Oxford : Oxford University Press, 2013)
This title presents a selection of the best current work in the history of early modern philosophy. It focuses on the 17th and 18th centuries - the extraordinary period of intellectual flourishing that begins, very roughly, with Descartes and his contemporaries and ends with Kant.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Philosophy, Modern